A história e cultura indígena pós lei 11.645/2008 nos anos iniciais do ensino fundamental: uma análise do manual para o (a) professor (a) do livro didático da coleção Pitanguá Mais - História - Baptista, Karen Cristina Santos (Universidade Federal de São Carlos, 2024)
This course completion work has the general objective of analyzing how indigenous themes are presented in the manuals for teachers of the textbooks in the Pitanguá Mais - História collection for the initial years of Elementary School. The analysis covers both the proposals for the students and the guidance provided to the teachers. The research, of a documentary and bibliographic nature, is also dedicated to the study of legal and normative documents that mark Brazilian education, such as Law nº 11,645/2008 and the National Common Curricular Base (BNCC), seeking to highlight how the mandatory implementation was of teaching indigenous History and Culture and its impacts on national education. As a result of this research, we aim to highlight the contributions of the Pitanguá Mais – História collection to the work with the theme of original peoples and also point out other resources to complement the work of the teacher in the classroom, always keeping in mind that teaching children about the different cultures and ethnicities present in the country is an important step in deconstructing prejudices and stereotypes.
Indigenous history and culture after law 11,645/2008 in the early years of elementary school: an analysis of the manual for teachers of the textbook from the Pitanguá Mais collection - History
Keywords: História; Livro didático; História e cultura indígena; Educação; Ensino fundamental; History; Textbook; Indigenous history and culture; Education; Elementary School; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM